Mengenal Konflik Akar Penolakan Dan Dampaknya Dalam Membangun Rumah Tangga Kristen - Pangarapen Sembiring (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
In building a household, conflicts often occur, one of the biggest conflicts heard by marriage counselors in the household is a statement like the following: